Border thinking and the modern Plaasroman: a study of three novels - Winfield, Matthew (African Studies, 2021)
In Afrikaans literature, the farm concept has a history of entanglement with ideals that are racist and nationalist. The early plaasroman (farm novel in Afrikaans) subgenre was a product of the 1920s and the 1930s, a period when Afrikaner nationalism was incipient. Later farm novelists brought new energy to the plaasroman during the second half of the twentieth century. In the modern plaasroman subgenre, challenges to racist-nationalist ideals are exhibited, along with ideals of the early plaasroman. The following study is an attempt to gauge whether, and the extent to which, three modern plaasromans are an expression of border thinking. These novels are Etienne Leroux's Seven Days at the Silbersteins, Etienne van Heerden's Ancestral Voices and Nadine Gordimer's The Conservationist. The paradigm of border thinking is chosen due to the similarities between its objectives, on the one hand, and the critical stance of the modern plaasroman, on the other hand. Both border thinking and the modern plaasroman can be described as a response to racial injustice and inequality. For this reason, it would seem that a study of modern plaasromans is well-suited as a context for the application of border thinking. Given that previous studies addressed challenges by modern plaasromans to racist and nationalist ideals, moreover, a study that deploys border thinking (focusing on racial injustice) is considered to be a valuable critical contribution. In order to determine whether these three novels are expressions of border thinking, this study first formulates three templates of ‘literary border thinking' (border thinking that is expressed in literature). Criteria that are derived from these templates are then used to determine whether, and the extent to which, these novels represent literary border thinking.